2008
DOI: 10.1108/09600030810882834
|View full text |Cite
|
Sign up to set email alerts
|

The impact of product design on supply chain risk: a case study

Abstract: Purpose -The purpose of this paper is to address the increasingly important issue of the impact of product design on supply chain risk management in an era of global supply arrangements. The need to include product design considerations in the development of global supply chain strategies is highlighted. Design/methodology/approach -The research methodology is based on an in-depth longitudinal case study of a major UK retailer. Data collection tools included observation of supplier meetings/workshops, semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 32 publications
4
112
0
1
Order By: Relevance
“…Fletcher (2008) reported that, more than ten years previously, M&S had been working to reduce the environmental impact of its clothing. M&S's specific competitive advantages in clothing arise from its trusted consumer reputation for quality (Worth, 2007), long established capabilities in considering environmental impacts (Blowfield, 2013), and its textile design and sourcing expertise (Khan et al, 2008). These enable M&S to impact the whole Use Chain for the environmental sustainability of the clothing system and able to 'simultaneously exercise demand-power upwards and supply-power downwards' (p362, Huber, 2008).…”
Section: Marks and Spencermentioning
confidence: 99%
“…Fletcher (2008) reported that, more than ten years previously, M&S had been working to reduce the environmental impact of its clothing. M&S's specific competitive advantages in clothing arise from its trusted consumer reputation for quality (Worth, 2007), long established capabilities in considering environmental impacts (Blowfield, 2013), and its textile design and sourcing expertise (Khan et al, 2008). These enable M&S to impact the whole Use Chain for the environmental sustainability of the clothing system and able to 'simultaneously exercise demand-power upwards and supply-power downwards' (p362, Huber, 2008).…”
Section: Marks and Spencermentioning
confidence: 99%
“…The design continuum, refers to how supply chain risk can be included at the initiation/design stage, such as the discussion of design led manufacturing (Khan et al, 2008;Manuj et al 2014) including the physical design of supply chain (i.e. store layout, plant planning, inventory management) (Christopher and Creazza, 2012).…”
Section: Supply Chain Risk Categoriesmentioning
confidence: 99%
“…[16]). A formal and structured approach should be adopted to risk management as suggested by researchers (e.g., [16], [17]). On the other hand, Colicchia and Strozzi (2012) indicated that there is a need for a comprehensive and dynamic approach to supply chain risk management.…”
Section: Problem Statementmentioning
confidence: 99%